Charge Transfer Complexes: Role of Water in the Dynamic Crystallization of CuTCNQ for Enhanced Redox Catalysis (TCNQ = Tetracyanoquinodimethane) (Adv. Mater. Interfaces 15/2017). Issue 15 (2nd August 2017) - Siu, Mark C.; Anderson, Samuel R.; Mohammadtaheri, Mahsa; Ahmed, Taimur; Walia, Sumeet; Ramanathan, Rajesh; Bansal, Vipul
Abstract : Vipul Bansal and co‐workers overcome the challenge in fabricating large dimension Cu(7, 7, 8, 8‐tetracyanoquinodimethane) (CuTCNQ) metal‐organic semiconductors in article number1700097 . The use of water‐acetonitrile bisolvent mixture instead of acetonitrile in conventional synthesis allows a dynamic control over the reaction equilibrium. This favours CuTCNQ crystallization and enables growth of highly redox active CuTCNQ structures exceeding 100 μm in length.